A DFT Study on the Structures and Energies of Isomers of 4‐Amino‐1, 3‐dinitro‐1, 2, 4‐triazol‐5‐one‐2‐oxide: New High Energy Density Compounds. Issue 3 (11th February 2013) - Ravi, Pasupala; Tewari, Surya P.; Ramaswamy, Ramakrishna
Abstract Isomers of 4‐amino‐1, 3‐dinitrotriazol‐5‐one‐2‐oxide (ADNTONO) are of interest in the contest of insensitive explosives and were found to have true local energy minima at the DFT‐B3LYP/aug‐cc‐pVDZ level. The optimized structures, vibrational frequencies and thermodynamic values for triazol‐5‐one N‐oxides were obtained in their ground state. Kamlet‐Jacob equations were used to evaluate the performance properties. The detonation properties of ADNTONO (D=10.15 to 10.46 km s−1, P=50.86 to 54.25 GPa) are higher compared with those of 1, 1‐diamino‐2, 2‐dinitroethylene (D=8.87 km s−1, P=32.75 GPa), 5‐nitro‐1, 2, 4‐triazol‐3‐one (D=8.56 km s−1, P=31.12 GPa), 1, 2, 4, 5‐tetrazine‐3, 6‐diamine‐1, 4‐dioxide (D=8.78 km s−1, P=31.0 GPa), 1‐amino‐3, 4, 5‐trinitropyrazole (D=9.31 km s−1, P=40.13 GPa), 4, 4′‐dinitro‐3, 3′‐bifurazan (D=8.80 km s−1, P=35.60 GPa) and 3, 4‐bis(3‐nitrofurazan‐4‐yl)furoxan (D=9.25 km s−1, P=39.54 GPa). The NH2 group(s) appears to be particularly promising area for investigation since it may lead to two desirable consequences of higher stability (insensitivity), higher density, and thus detonation velocity and pressure.